Machining Analysis on a Pin Chuck by Using Mastercam Software - Azahri, Mohamad Izzat; Haffidzudin Hehsan; Muharam Rafidi Jaafar (Progress in Engineering Application and Technology, 2022)
Machining is a vital manufacturing process that is used in a variety of applications. It is the process of removing material from a workpiece using power-driven machine tools to shape it into the desired design. A cylindrical shape is a product that needs to be transformed into a pin chuck design. The significance of this research is to learn more about the Mastercam software and the machining analysis of the pin chuck. The Mastercam software can design and develop a simulation for the product. This study was conducted to design the pin chuck, simulate the toolpath process using Mastercam software and find the relationship between spindle speed and machining time. Carbide is a cutting tool to be used to operate the cylindrical material. Furthermore, three parameters that influence machining time are spindle speed, feed rate, and plunge rate. In the simulation Mastercam software, these parameters will be observed to see how they may affect the machining time. Moreover, the relationship between these parameters have not been yet established based on the simulation analysis. Mastercam software is used to complete the pin chuck process. There were numerous steps to create the product, including design, lathe machine operation, toolpath processes, and more. Backplot and verify operations are required after completing the toolpath processes. Simulate to evaluate the machining time of the pin chuck process. The analysis aims to investigate the relationship between spindle speed and machining time. The spindle speed has the greatest influence on the differences in machining time that occur. As a result, the spindle speed is inversely proportional to the machining time. It is because the higher the spindle speed, the shorter the machining time. Lastly, in terms of toolpath types processes, the finishing process has the shortest machining time compared to the others.